Amanah and Muslim identity: relationships with religious and psychological adjustment in Malaysia - Tekke, Mustafa; Watson, Paul J.; Kayadibi, Saim; Chen, Zhuo Job (Springer, 2018)
Amanah refers to the accountability of Muslims to their community. In Malaysian Muslim university students (N = 209), an Amanah Scale predicted a stronger sense of identity along with more adaptive religious and psychosocial functioning. Multiple regression analyses identiﬁed Accountability to Society as especially inﬂuential, but Accountability to Allah exhibited at least some problematic implications. Amanah mediated Identity linkages with some measures of religious and psychological adjustment, but also suppressed Identity relationships with greater self-knowledge and lower anxiety. These data conﬁrmed the importance of communal commitments in Muslim mental health, suggested that accountability may have limited liabilities as well as more obvious psychosocial advantages, and identiﬁed possible complexities in the assessment of Accountability to Allah.